Assessment of the UN’s Role in Peacekeeping and Development in East Timor - Ridha Amalia; Syuryansyah Syuryansyah (Andalas Journal of International Studies (AJIS), 2025)
This article examines the United Nations' (UN) intervention in East Timor, highlighting its success as a model of international peacekeeping in the context of internal conflict. The study uses a qualitative approach with a descriptive analysis method, drawing on a literature review of various secondary sources, including UN reports, scholarly journals, and previous research. The study examines three primary aspects: the international context and the foundations of intervention based on peacekeeping and the Responsibility to Protect (R2P); the perspectives of the East Timorese community regarding the UN intervention; and an evaluation of peacekeeping missions, including UNAMET, UNTAET, and UNMIT. The findings reveal that while the UN operations in East Timor were generally successful in supporting the transition to independence and creating stability, challenges in achieving sustainable development and empowering local communities remain significant tasks. This study highlights the importance of adopting a responsive approach to local contexts to ensure the sustainability of peace. The experience in East Timor offers strategic insights for the implementation of future international peacekeeping missions.